RESPON KONSUMEN TAHU TERHADAP KENAIKAN HARGA KEDELAI DI KABUPATEN BANTUL - -, Sriyadi (MAPETA, 2010)
This research aims to describe the consumer attitude and behavior toward the increase of the soybean price and to know the consumer response toward the increase of the soybean price taken from the attitude and behavior change point of view. The site of the research was intentionally chosen in Bantul Region since therewere lot of tofu vendors in the region, and there were 150 samples of consumers. Description was used to describe the consumer attitude, behavior, and response. The result of the analysis showed that the consumer response toward the increase of the soybean price remained the same, because all of the consumers gave theneutral response. The result of this research also showed that the price of the tofu remained the same but the size was smaller so that the price was still affordable for the consumers. It is recommended for the tofu producers if the soybean price increases, they should not increase the tofu price but make the tofu size smaller.Key words : attitude, behavior, response, soybean, and consumer.